Pengaruh Knowledge Sharing, Absortive Capacity dan Organizational Learning Capability Terhadap Innovation Performance Pada PT. Perkebunan Nusantara IV (Persero) Medan - M Mario Boy Sandy; Alvin Fahlevi; Sopi Pentana (Cattleya Darmaya Fortuna, 2023)
The formulation of the problem in this study is whether knowledge sharing has an effect on the Performance of the State Civil Apparatus (ASN) at PT. Perkebunan Nusantara IV (Persero) Medan. Does absortive capacity affect the performance of the State Civil Apparatus (ASN) at PT. Perkebunan Nusantara IV (Persero) Medan. Does organizational learning capability affect the performance of the State Civil Apparatus (ASN) at PT. Perkebunan Nusantara IV (Persero) Medan. Does knowledge sharing, absortive capacity and organizational learning capability affect the performance of the State Civil Apparatus (ASN) at PT. Perkebunan Nusantara IV (Persero) Medan. The total population in this study amounted to 389 people, and by using the Slovin formula obtained a sample of 80 people. The analysis technique used is multiple linear regression. The results showed that knowledge sharing had a positive and significant effect on innovation performance at PT. Perkebunan Nusantara IV (Persero) Medan. Absortive capacity has no effect on innovation performance at PT. Perkebunan Nusantara IV (Persero) Medan. Organizational learning capability has a positive and significant effect on innovation performance at PT. Perkebunan Nusantara IV (Persero) Medan. Knowledge sharing, absortive capacity and organizational learning capability have a positive and significant effect on innovation performance at PT. Perkebunan Nusantara IV (Persero) Medan.